Comparison of Isokinetic Strength Parameters of Quadriceps in Athletes and Non-Athletes - Aamir Gul Memon; Muhammad Faheem Afzal; Muhammad Manan Haider Khan; Shard Kumar Bansari; Aqeel Saeed; Muhammad Sanaullah (JLUMHS, 2023)
OBJECTIVE: To compare the quadriceps isokinetic strength parameters of athletes and non-athletes. METHODOLOGY: The cross-sectional study was conducted from July to December 2019 at the Pakistan Sports Board, Islamabad. The sample size was 81, selected through a non-probability convenience sampling technique and calculated by the Rao Soft tool. The 41 participants were in the athletes' group, and 40 were in the non-athletes' group. Individuals with a history of sprain, strain, or fracture in the lower limbs within the last six months were excluded. The self-structured questionnaire includes demographic data, waist-to-hip ratio, thigh circumference, peak torque values and agility t-test score. The isokinetic strength of the right lower limb (RLL) was measured via Biodex system Pro 3. Data was analyzed through SPSS 22, and an independent t-test was applied for analysis between groups. Pearson test was used for the correlation coefficient. RESULTS: Athletes had significantly higher quadriceps muscle strength than non-athletes (p<0.001), indicating the positive impact of regular sports participation and physical training. Quadriceps peak torque positively correlated with thigh circumference (r=0.60, p<0.001), consistent with previous studies. Surprisingly, athletes exhibited a weak to moderate negative correlation between quadriceps peak torque and agility (r=-0.35, p<0.05), suggesting a potential trade-off between muscle mass and agility performance. Increased muscle bulk may compromise speed and flexibility. CONCLUSION: Athletes demonstrated superior quadriceps muscle strength, emphasizing the positive influence of sports involvement and physical training; thigh circumference positively correlated with Quadriceps peak torque, and Agility negatively correlated with quadriceps peak torque.